Clinical spectrum of hypothyroidism: a cross sectional study in Puducherry, South India - M., Darshan Savery; C., Vijay Prasad; R., Vishnu Prasad (International Journal of Research in Medical Sciences, 2016)
Background: Hypothyroidism is characterised by underactive thyroid gland where there is reduced synthesis and secretion of thyroid hormones by the gland. With nearly one fifth of the population affected by hypothyroidism it is important to understand the clinical presentation of the disease. The present study aims to explore various clinical signs and symptoms of patients with hypothyroidism in Puducherry, South India. Methods: The study was carried out as a cross sectional study in a tertiary care medical college hospital, Puducherry among 213 patients who are admitted for various reasons and found to have hypothyroidism on laboratory investigations. With help of specialists in various fields all the patients were evaluated thoroughly and findings of the history and examination were noted down. Data entry was done in Epi Data version 3. Means and proportions were calculated using the software SPSS version 21. Results: Most of the hypothyroid patients (168/213) were females, giving a female: male ratio of approximately 3.4: 1. Primary hypothyroidism was found in most of the study participants (91%) and sub clinical hypothyroidism was seen in 6.2% of the patients. Commonest clinical presentation of the hypothyroid patients were fatigue (83.6%), weight gain (66.7%), were dry/coarse skin (52.1%) and voice change (50.7%). Conclusions: The commonest symptom being fatigue and weight gain while the commonest clinical sign was dry skin and voice change.